Theriotopologies: Review of Lorella Bosco and Micaela Latini, eds., Animals and Humans in German Literature, 1800–2000 - Salzani, Carlo (Humanimalia, 2022)
Review of Lorella Bosco and Micaela Latini, eds. Animals and Humans in German Literature, 1800–2000: Exploring the Great Divide. Newcastle upon Tyne: Cambridge Scholars Publishing, 2020. xviii + 160 pp. £58.99, hb.